Steganography Technique and Modification of Substitution Cipher Using ASCII Code and Fibonacci Sequences - Pradana, Musthofa Galih; Saputro, Pujo Hari; Pamekas, Bondan Wahyu (CSRID (Computer Science Research and Its Development Journal), 2021)
Cryptography is widely used to secure data and information so that it is not easily misused by parties who are not interested in the data. One type of cryptographic algorithm is Caesar Cipher and Vigenere Cipher. Both of these algorithms are classic cryptographic algorithms that need to be modified so that they become more optimal in the data security process. The first modification is to modify the Vigenere key using Fibonacci. In general, Vigenere Cipher will repeat the same keyword to complete the number of characters that are lacking so that the number of characters is the same as the number of characters in the plaintext. The second modification is to change or convert plaintext letters into ASCII letters so that the code is more difficult to solve. After the ASCII conversion process is done, the next results will be converted back in Hexa letters. In addition to the two modifications made, the steganography technique is also added by hiding the code behind the media in the form of images. Images that are sampled will be renamed and stored in different places.